The Effect of "KIS" (Social Interaction Communication) Application on the Augmentative Alternative Communication to Improve Communication for Down Syndrome Students - Sundari, Tita; Aprilia, Imas Diana (Journal of ICSAR, 2024)
This research develops AAC for students with Down syndrome using the "KIS" application media. The purpose of making this media is to help students with Down syndrome who have difficulty communicating. The application is designed using symbols to learn to understand and express themselves using predetermined symbols. This study used an experimental, single-subject research (SSR) approach with an A-B-A design. the subject in this study was one of the Down syndrome students with communication barriers. The target behavior of the research is communication skills. Data collection techniques are obtained by observation, and action tests. The data analysis used is a descriptive system with a graphical presentation. The results showed that the "KIS" application can help improve the subject's communication skills. Based on the increase in target behavior, namely the increase in the subject's communication skills in the initial condition, the results obtained were 44.4% increased to 72.2%.